Low grade malignant peripheral nerve sheath tumour: varied cytological and histological patterns. Issue 11 (4th November 2003) - Yamaguchi, U; Hasegawa, T; Hirose, T; Chuman, H; Kawai, A; Ito, Y; Beppu, Y
Abstract : Background: A small number of malignant peripheral nerve sheath tumours (MPNSTs) are low grade, and the nature of these low grade tumours has never been systematically assessed. Aims: To describe the clinicopathological, immunohistochemical, and ultrastructural features of low grade MPNST and to discuss the main differential diagnoses. Methods: Four cases of low grade MPNST were studied, including one coexistent with neurofibromatosis type 1. The tumours were analysed with respect to nuclear atypia, cellularity, nuclear enlargement, hyperchromasia, mitotic rate, and necrosis. Immunohistochemistry was performed by standard techniques, and an ultrastructural study was performed on one tumour. Results: The ages of the patients ranged from 32 to 72 years (mean, 58). Two were male and two were female. Three tumours occurred in the deep tissue, including one in the retroperitoneum, and one was located in the dermal and subcutaneous tissue. The maximum diameters of the tumours ranged from 3.5 to 8.0 cm. Microscopically, all tumours showed moderate hypercellularity, an increased nuclear to cytoplasmic ratio, and hyperchromasia, but exhibited varied growth patterns, including those that were atypical neurofibroma-like, low grade fibromyxoid sarcoma-like, low grade epithelioid, and haemangiopericytoma-like. All tumours showed immunoreactivity for S-100 protein and vimentin. Conclusions: These findings suggest that careful clinical and histological evaluation, along with S-100 protein immunostaining, are essential for the accurate diagnosis of low grade MPNST.